A Comprehensive Review of Atmosphere-Breathing Electric Propulsion Systems. (7th October 2020) - Zheng, Peng; Wu, Jianjun; Zhang, Yu; Wu, Biqi
Abstract : To develop the satellites for a low-Earth-orbit environment, atmosphere-breathing electric propulsion (ABEP) systems have become more attractive to researchers in the past decade. The system can use atmospheric molecules as the propellant to provide thrust compensation, which can extend the lifetime of spacecraft (S/C). This comprehensive review reviews the efforts of previous researchers to develop concepts for ABEP systems. Different kinds of space propulsion system are analysed to determine the suitable propulsion for atmosphere-breathing S/C. Further discussion about ABEP systems shows the characteristic of different thrusters. The main performance of the ABEP system of previous studies is summarized, which provides further research avenues in the future. Results show great potential for thrust compensation from atmospheric molecules. However, the current studies show various limitations and are difficult to apply to space. The development of ABEP needs to solve some problems, such as the intake efficiency, ionization power, and electrode corrosion.